The Role of Islamic Religious Education Teachers in Preventing Bullying Behavior at SMP IT Darur Rasyid Aceh Singkil - Sartina Sartina; Nurfadilah Tanjung; Sri Hidayati; Hasrian Rudi Setiawan (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
This study aims to determine the role of Islamic Religious Education teachers in preventing bullying behavior at SMP IT Darur Rasyid Aceh Singkil. The research employs a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation. The results show that Islamic Religious Education teachers play a crucial role in preventing bullying through three main aspects: (1) educative role, by teaching moral values and Islamic teachings that forbid harming others; (2) guidance role, by providing Islamic counseling and support to students involved in bullying; and (3) exemplary role, by serving as role models through daily behavior and attitudes. Preventive efforts are also implemented through religious activities such as Qur’an recitation, congregational prayers, and short sermons that instill compassion and Islamic brotherhood. This study concludes that Islamic Religious Education teachers significantly contribute to creating a harmonious, religious, and bullying-free school environment.